Elevated Serum SIRT 2 May Differentiate Parkinson’s Disease From Atypical Parkinsonian Syndromes - Singh, Amrendra Pratap; Ramana, G.; Bajaj, Teena; Singh, Vishwajeet; Dwivedi, Sadanand; Behari, Madhuri; Dey, A. B.; Dey, Sharmistha (Frontiers in Molecular Neuroscience, 2019)
Atypical Parkinson Syndromes (APSs) often have symptoms that overlap with those of Parkinson's disease (PD), especially in early in disease, making these disorders difficult to diagnose. Previous studies have demonstrated association of oligomeric α-synuclein (α-Syn), a key element in the pathogenesis of PD, with Sirtuin (SIRT)2 proteins for modulating PD. We aimed to evaluate SIRT proteins expression in serum of PD patients and compare it with APSs and normal elderly control (GC); and correlate with α-Syn. SIRT proteins expression was evaluated in sera of 68 PD; 34 APS and 68 GC without any neuro-psychiatric illness as controls by Surface Plasmon Resonance. SIRT2 expression was correlated with α-Syn in PD and GC. Significant (p<0.0001) differences were observed between serum SIRT2 concentration in PD and APS and GC; and between APS and GC. ROC analysis revealed the strong cut off value to differentiate PD from APS and GC and also APS from GC. Significant correlation was observed among SIRT2 levels in early PD patients with UPDRS, H and Y and increase duration of disease. In addition, a strong positive correlation of SIRT2 with α-Syn (p<0.0001) was observed. However, no such difference was detected for serum SIRT1 in cases of PD and APS; and GC. The present study is the first to report elevated serum SIRT2 in PD. The study also provided a simple test to distinguish PD from APS and may have translational utility for diagnosis.